2020
DOI: 10.1155/2020/9519072
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Peripheral Neutrophil Transcriptome in Newly Diagnosed Type 2 Diabetes Patients

Abstract: Aim. There are increasing evidence demonstrating that neutrophil-mediated inflammation plays a role in the etiology of type 2 diabetes. However, the molecular mechanisms by which neutrophils contribute to type 2 diabetes remain largely unknown. The aim of the present work was to identify possible changes in circulating neutrophils to better elucidate neutrophil involvement in human type 2 diabetes. Methods. Patients newly diagnosed with type 2 diabetes (n=5) and age- and sex-matched healthy controls (n=5) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…In general, T2D neutrophils tended to have a stronger response to RvE1 treatment, particularly at higher, clinically relevant, RvE1 doses (Figure 3). Without any RvE1 treatment, we observed higher levels of pro-in ammatory cytokines P-Selectin and TNF-α among T2D compared to healthy neutrophils, consistent with recent evidence for enriched cytokine expression in T2D neutrophils (44), though levels of pro-in ammatory MIP-1β, IL-8, and sICAM-1 cytokines were decreased in T2D neutrophils (Figure 4). As cytokines have complex and often overlapping roles in proand anti-in ammatory pathways, the relative contribution of each cytokine to neutrophil dysfunction in T2D will require further investigation.…”
Section: Discussionsupporting
confidence: 90%
“…In general, T2D neutrophils tended to have a stronger response to RvE1 treatment, particularly at higher, clinically relevant, RvE1 doses (Figure 3). Without any RvE1 treatment, we observed higher levels of pro-in ammatory cytokines P-Selectin and TNF-α among T2D compared to healthy neutrophils, consistent with recent evidence for enriched cytokine expression in T2D neutrophils (44), though levels of pro-in ammatory MIP-1β, IL-8, and sICAM-1 cytokines were decreased in T2D neutrophils (Figure 4). As cytokines have complex and often overlapping roles in proand anti-in ammatory pathways, the relative contribution of each cytokine to neutrophil dysfunction in T2D will require further investigation.…”
Section: Discussionsupporting
confidence: 90%
“…3 ). Without any RvE1 treatment, we observed higher levels of pro-inflammatory cytokines P-Selectin and TNF-α among T2D compared to healthy neutrophils, consistent with recent evidence for enriched cytokine expression in T2D neutrophils [ 44 ], though levels of pro-inflammatory MIP-1β, IL-8, and sICAM-1 cytokines were decreased in T2D neutrophils (Fig. 4 ).…”
Section: Discussionsupporting
confidence: 89%
“…Further, a recent study in adipose tissue showed that apolipoprotein M expression was decreased in T2D and obese individuals compared to lean individuals [ 43 ], further indicating a role for downregulation of genes in diabetes pathogenesis. A recent study investigating neutrophil gene expression in a small number of newly diagnosed diabetics compared to controls also observed neutrophil dysregulation, with > 15% of neutrophil genes differentially expressed in recently diagnosed T2D, ~ 60% of which were upregulated [ 44 ]. These vast differences in gene expression may be explained by neutrophil heterogeneity in a small number of samples, failure to fully exclude monocytes, or differences in neutrophil gene expression at onset of T2D compared to established disease.…”
Section: Discussionmentioning
confidence: 99%
“…Kaizer et al [ 15 ] also reported that type 1 DM and T2D shared pathogenic mechanisms, such as overexpression of IL1B (probably due to hyperglycemia). Moreover, Lin et al [ 16 ] performed RNA sequencing for neutrophils isolated from the blood of T2D patients and found that genes dysregulated in these patients were enriched in cytokine–cytokine receptor interactions, as well as nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), tumor necrosis factor, cell adhesion molecule, Toll-like receptor, and chemokine signaling. In the OPTIMED study, whole transcriptome of T2D blood samples further revealed that genes with altered expression after anti-diabetic treatment with metformin were involved in the improvement of energy metabolism, the modulation of inflammation, and the inhibition of cancer progression [ 17 ].…”
Section: Introductionmentioning
confidence: 99%